Recent Approach for an Effective Treatment of Mucormycosis and Future Directions - Singh, Sushil Kumar; Islam, Md Moidul; Pancholi, Shyam Sunder (Anti-Infective Agents, 2026)
Mucormycosis is an aggressive and often fatal fungal infection, posing a significant challenge in immunocompromised patients, particularly those with diabetes, cancer, or post-organ transplantation. Despite available antifungal treatments such as amphotericin B, posaconazole, and isavuconazole, mortality rates remain high, highlighting the need for early diagnosis and aggressive intervention. This review explores current therapeutic strategies, including antifungal therapy, and the critical role of surgical intervention in improving outcomes. Additionally, it examines innovative drug delivery systems, such as nanoparticle-based formulations and liposomal encapsulation, designed to enhance drug efficacy while minimizing toxicity. The recent surge in mucormycosis cases, particularly during the COVID-19 pandemic, emphasizes the urgent need for improved awareness, early detection, and optimized treatment protocols. Advancements in diagnostic techniques and emerging therapeutic approaches offer hope for better management of this deadly infection. By analyzing current trends and future directions, this article advocates for a multidisciplinary approach that combines clinical expertise with cutting-edge research. Strengthening collaborative efforts in diagnosis, treatment, and drug development is essential to reducing mortality and improving patient outcomes in this rare but life-threatening disease.
Keywords: amphotericin B